ANALISIS POLA KOMUNIKASI DALAM INTERAKSI EDUKATIF ANTARA GURU DAN SISWA DALAM PROSES PEMBELAJARAN SOSIOLOGI - Suriyani, . (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThe aim of this study is to find out how the pattern of communication as an action, communication pattern as an interaction and communication pattern Â as a transaction in the process of learning in sociology. This study employs descriptive method. The techniques that are used for collecting data are observation, interview, and documentation. The results showed that communication pattern as an action is one-way communication, in which the teacher was more active while the students tended to be more passive, this type of communication was done at beginning of the class, conveying material and question and answer section. The pattern of communication as an interaction is two-way communication in which the teacher and the students were equally active in learning activities, this communication was done when giving feedback as well as question and answer section. The pattern of communication as a transaction was found as a multiple-way communication, which was not only between the teacher and the student, but also among the students one another, this communication was done during group discussion and question and answer section. Keywords: communication pattern, educative interaction, learning process